Electropulse Selective Disintegration of Mountain Breeds, Products of Technical Rubber and Extraction of Substances from Vegetative Raw Material; International Conference on Pulsed Power Applications : PPA 2001, University of Applied Sciences Gelsenkirchen, March 27-29, 2001 - Kurets (Kuretz) V. I. Valery Isaakovich; Dulzon A. A. Alfred Andreevich; Tarakanovsky E. N. Eduard Nikolaevich; Lobanova G. L. Galina Leonidovna; Filatov G. P. Gennady Petrovich; Soloviev M. A. Mikhail Aleksandrovich; Barskaya A. V. Anna Valerievna (2001, 2001)
В фонде НТБ ТПУ отсутствует